A numerical and experimental study of hydronic heating for road deicing and its energy flexibility. (22nd August 2022) - Saberi Derakhtenjani, Ali; Athienitis, Andreas
Abstract : The use of deicing salts and other anti-skid measures typically adopted by highway maintenance services have many limitations such as applicable temperatures, location of storage facilities, ease of access to road section and, in the case of salts, infrastructure and environmental damage. An alternative solution that offers several advantages is the implementation of hydronic heating systems implemented under the road surfaces. Hydronic deicing may eliminate the need to add salts to road surfaces, thus prolonging the lifetime of infrastructure and significantly reducing maintenance costs. This article presents a methodology to develop low-order models for hydronic deicing slabs with significant thermal mass along with validation in an environmental chamber. The models are utilized to analyze the thermal dynamics of different pipe depths for hydronic deicing slab of a transportation infrastructure in Montreal, Canada. A key objective of the presented study is preheating the slab to reach a surface temperature of about 2 °C before the precipitation to greatly reduce the risk of ice formation. The magnitude of time delay to reach the required surface temperature for deicing for different slab piping configurations and system capacity is evaluated by means of a reduced-order lumped parameter model. The model is then utilized to study an energy flexibility strategy based on thermal response delay of the slab as a function of piping distance from surface to significantly reduce the heating load during the peak demand period.